2020
DOI: 10.1186/s13045-020-00906-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hippo-YAP signaling by insulin-like growth factor-1 receptor in the tumorigenesis of diffuse large B-cell lymphoma

Abstract: Background: Hippo-Yes-associated protein (YAP) signaling is a key regulator of organ size and tumorigenesis, yet the underlying molecular mechanism is still poorly understood. At present, the significance of the Hippo-YAP pathway in diffuse large B-cell lymphoma (DLBCL) is ill-defined. Methods: The expression of YAP in DLBCL was determined in public database and clinical specimens. The effects of YAP knockdown, CRISPR/Cas9-mediated YAP deletion, and YAP inhibitor treatment on cell proliferation and the cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…The Hippo-YAP signaling pathway is known as a pivotal regulator of organ growth and tissue regeneration ( Moya and Halder, 2019 ). In recent years, there have been an increasing number of regenerative medicine strategies in different organs targeting this pathway ( Aharonov et al., 2020 ; Aloia et al., 2019 ; Alsamman et al., 2020 ; Brusatin et al., 2018 ; Cheung et al., 2020 ; Gilbert-Honick et al., 2020 ; Hageman et al., 2020 ; Li et al., 2020 ; Sprangers et al., 2020 ; Zhou et al., 2020 ). Thus, the Hippo-YAP signaling pathway has great potential and is worthy of further study to better promote the development of regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo-YAP signaling pathway is known as a pivotal regulator of organ growth and tissue regeneration ( Moya and Halder, 2019 ). In recent years, there have been an increasing number of regenerative medicine strategies in different organs targeting this pathway ( Aharonov et al., 2020 ; Aloia et al., 2019 ; Alsamman et al., 2020 ; Brusatin et al., 2018 ; Cheung et al., 2020 ; Gilbert-Honick et al., 2020 ; Hageman et al., 2020 ; Li et al., 2020 ; Sprangers et al., 2020 ; Zhou et al., 2020 ). Thus, the Hippo-YAP signaling pathway has great potential and is worthy of further study to better promote the development of regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is evidenced that, DLBCL samples with high expression rate of YAP shows poor prognosis. A recent study demonstrated that insulin-like growth factor-1 receptor (IGF-1R) acted as an upstream negative regulator of Hippo-YAP signaling [37]. It is extremely interesting to note that IGF-1R inhibition resulted in decreased activation of Hippo-YAP signalling in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…An amplified expression of YAP was remarkably associated with lymphoma progression and a bad outcome. A knockdown of YAP expression reduced cell growth and caused cell-cycle arrest in DLBCL cells [ 128 ].…”
Section: Yap and Hematological Malignanciesmentioning
confidence: 99%